'It doesn't reveal itself': erosion and collapse of the image in contemporary visual practice*. (2nd September 2018) - Mieves, Christian
ABSTRACT: The article explores the extent to which 'pictorial art' resists legibility, transparency and coherence. The analysis of three artistic case studies, Idris Khan, Maria Chevska and Jane and Louise Wilson, serves to investigate established hierarchies in our perception of visual referents. In the discussion, the article inquires the means of erosion, veiling and dissemblance as ways to critique assumption of the homogeneity of the image. All artists cast a view of the external world by diverting it, defacing it and distancing themselves from the external environment. However, the distancing is never disconnected from the everyday and never succumbs to abstraction. The article argues that the crisis of the image offers a productive framework that allows artists to draw attention to the absence of logical structure and the instability of the visual sign.